2021
DOI: 10.7150/jca.49409
|View full text |Cite
|
Sign up to set email alerts
|

Identification of marker genes and cell subtypes in castration-resistant prostate cancer cells

Abstract: The diverse tumor cell populations may be the critical roles in relapse and resistance to treatment in prostate cancer patients. This study aimed to identify new marker genes and cell subtypes among castration-resistant prostate cancer (CRPC) cells. We downloaded single-cell RNA seq profiles (GSE67980) from the Gene Expression Omnibus (GEO) database. Principal component (PC) analysis and t-Distributed Stochastic Neighbor Embedding (TSNE) analysis were performed to identify marker genes. CRPC cells were cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Interestingly, several DMEGs (e.g., TBX15 , REG1A , and HBB ) were found in all three regions, indicating that these genes may have transcriptional differences caused by differential methylation. Previous reports have shown that TBX15 expression can be used as a prognostic marker for HCC ( Morine et al, 2020 ), and HBB has been reported to play a key role in prostate cancer differentiation and in a variety of important biological pathways (e.g., iron metabolism) ( Chen and Sun, 2021 ; Lin et al, 2021 ). Based on the present expression data, we identified four different regulatory gene sets in the three DNA regions, for a total of 31 DMEGs ( Figure 4E ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, several DMEGs (e.g., TBX15 , REG1A , and HBB ) were found in all three regions, indicating that these genes may have transcriptional differences caused by differential methylation. Previous reports have shown that TBX15 expression can be used as a prognostic marker for HCC ( Morine et al, 2020 ), and HBB has been reported to play a key role in prostate cancer differentiation and in a variety of important biological pathways (e.g., iron metabolism) ( Chen and Sun, 2021 ; Lin et al, 2021 ). Based on the present expression data, we identified four different regulatory gene sets in the three DNA regions, for a total of 31 DMEGs ( Figure 4E ).…”
Section: Resultsmentioning
confidence: 99%
“…According to a related study, HBB may be a novel tumour suppressor gene in anaplastic thyroid cancer (ATC) ( Onda et al, 2005 ). PCa was found to have high HBB variations, and it was also considered a potential prognostic biomarker ( Davalieva et al, 2017 ; Lin et al, 2021 ). And high HBB expression may promote neutrophils infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Using TCGA methylation and RNA-seq data, Xu et al performed an epigenetic integrative analysis between normal and PCa tissue, in order to detect the pathways in which DNA methylation-driven genes were significantly enriched [ 35 ]. More recently, in the study by Lin et al, using single-cell RNA-seq profiles, the authors identified new signature genes and cell subtypes among CRPC cells [ 36 ]. All this evidence brings out a clear role for epigenetic regulation in PCa control.…”
Section: Epigenetic Alterations In Prostate Cancermentioning
confidence: 99%